MOS current mode circuits analysis, design, and variability. - Hassan, H. (IEEE Transactions on VLSI systems)
The interest in MOS current-mode logic (MCML) is increasing because of its ability to dissipate less power than conventional CMOS circuits at high frequencies, while providing an analog friendly environment. Moreover, automated design methodologies are gaining attention by circuit designers to provide shorter design cycles and faster time to market. This paper provides designers with an insight to the different tradeoffs involved in the design of MCML circuits to efficiently and systematically design MCML circuits. A comprehensive analytical formulation for the design parameters of MCML circuits using the BSIM3v3 model is introduced. In addition, a closed-form expression for the noise margin of two-level MCML circuits is derived. In order to verify the validity of the analytical formulations, an automated design methodology for MCML circuits is proposed to overcome the complexities of the design process. The effectiveness of the design methodology and the accuracy of the analytical formulations are tested by designing several MCML benchmarks built in a 0.18-μm CMOS technology. The error in the required performance in the designed circuits is within 11% when compared to HSPICE simulations. A worst case parameter variations modeling is presented to investigate the impact of variations on MCML circuits as well as designing MCML circuits for variability. Finally, the impact of variations on MCML circuits is investigated with technology scaling and different circuit architectures.